Usability Matters: User Experiences of Visually Impaired Older Adults - Sili, Miroslav; Gira, Matthias; Mayer, Christopher (Human-Computer Interaction. User Interface Design, Development and Multimodality, 2017)
Many applications and services are not accessible for all people. Especially visually impaired and blind people are often excluded or severely limited in their use. This is even more severe, when we consider the Active and Assisted Living (AAL) domain and its primary target group of older adults, additionally suffering from other age related physical and cognitive impairments, and with limited technological experience. In this paper we present the user centered design process of reaching an in- and outdoor navigation solution, suitable for this target group, mitigating shortcomings of conventional applications. In total we conducted six user involvement and User Experience (UX) evaluation actions with different approaches and engaging different stakeholders. The paper describes the gradual realization of such an application prototype, accessible to visually impaired and blind people, highlighting the impact of the user centered design approach at all stages.